Populism in Power: Discourse and Performativity in SYRIZA and Donald Trump - Venizelos, Giorgos (My University, 2024)
Shifting attention away from policy achievements and effects on democracy, this book focuses on the charismatic function of populist discourse – comprising antagonistic narratives, transgressive style and appeals to the common people. The book puts forward an integrative approach that brings together discourse analysis, analysis of digital media, in-depth interviews and ethnographic methods, and places into comparative perspective the cases of SYRIZA in Greece and Donald Trump in the United States. Theorising populism through the lens of collective identification, Venizelos places the rhetorical and emotional dynamics of populist performativity at the core of the analysis, offering a rigorous yet flexible conceptulisation of populism in power. Against theoretical expectations, findings suggest that both SYRIZA and Trump retained, to different degrees, their populist character in power, although their style and vision differed vastly. This book urges researchers, journalists and politicians to adopt a reflexive approach to analysing the political implications of populism for politics, polity and society, and to challenge the normatively charged definitions that are uncritically reproduced in the public sphere. It will appeal to researchers of political theory, populism, comparative politics, sociologists and ethnographers.
Keywords: populism; Donald Trump; SYRIZA; Performativity; Discourse; Social Movements; Collective Identity; Anti-Populism; Left-wing politics; Right-wing politics; comparative politics; political communication; political theory